Influence of Gamification Elements on Students' Academic Performance - Moses Adeleke Adeoye (Universitas Pendidikan Indonesia, 2023)
Playing games is an important part of a child's cognitive and social development. Students learn more when they are allowed to play and engage in hands-on activities rather than being forced to memorize knowledge (formulas) from books. Enjoyable components must be incorporated into their classes to maintain their attention and increase their performance. The great benefits that gamification offers must be integrated into the basic level of education to limit the easily bored span. Appropriate integration of gamification into classroom activities could raise a positive effect on students' performance and promote a positive attitude toward learning. This study could provide teachers with information and awareness on innovative instructional approaches that can boost students' engagement, motivation, and performance while learning. It can also serve as an eye-opener for teachers in other fields of learning to explore and adopt better instructional approaches to teaching to improve student performance. Training of teachers on the use of gamification-based teaching should be integrated into our educational sector. This research was conducted to determine the influence of gamification elements on student academic achievement.